2012
DOI: 10.1155/2012/201492
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Degradation of Organic Dye by Sol‐Gel‐Derived Gallium‐Doped Anatase Titanium Oxide Nanoparticles for Environmental Remediation

Abstract: Photocatalytic degradation of toxic organic chemicals is considered to be the most efficient green method for surface water treatment. We have reported the sol-gel synthesis of Gadoped anatase TiO2nanoparticles and the photocatalytic oxidation of organic dye into nontoxic inorganic products under UV irradiation. Photodegradation experiments show very good photocatalytic activity of Ga-doped TiO2nanoparticles with almost 90% degradation efficiency within 3 hrs of UV irradiation, which is faster than the undoped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 61 publications
2
24
0
Order By: Relevance
“…TiO 2 is a versatile material that has been used in many applications, such as gas sensors, solar cells, photocatalytic layers for self-cleaning glass, photocatalytic degradation of organic wastes, hydrogen production, storage media, optical coatings for filters and waveguides, and various biological-and health-related applications [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66]. Since the early twentieth century, titanium dioxide (TiO 2 ) has been widely used as a pigment in sunscreens, paints, ointments, toothpaste, etc.…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 is a versatile material that has been used in many applications, such as gas sensors, solar cells, photocatalytic layers for self-cleaning glass, photocatalytic degradation of organic wastes, hydrogen production, storage media, optical coatings for filters and waveguides, and various biological-and health-related applications [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66]. Since the early twentieth century, titanium dioxide (TiO 2 ) has been widely used as a pigment in sunscreens, paints, ointments, toothpaste, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The specific vibration modes are located at 148 cm −1 (Eg), 399 cm −1 (B1 g), 512 cm −1 (B1g + A1g), and 630 cm −1 (Eg), indicating the presence of the anatase phase in all of these samples. The absence of Raman active band around 318 cm −1 , which would be characteristic for Ga 2 O 3 [9], shows the absence of crystalline gallium oxide. Unfortunately, neither Raman spectroscopy is sufficiently sensitive to amorphous (or highly defective) phases.…”
Section: Journal Of Nanomaterialsmentioning
confidence: 99%
“…Banerjee et al [9] reported on the oxidation of organic dye (Rhodamine B) into nontoxic inorganic products under UV irradiation using a Ga-doped TiO 2 synthesised by solgel technique. Pure TiO 2 , single-doped, and Ga+N codoped titania nanoparticles were successfully prepared by sol-gel method.…”
Section: Journal Of Nanomaterialsmentioning
confidence: 99%
“…Titanium dioxide (TiO 2 ) NPs in anatase form are often used as photocatalyts. Anatase NPs doping with Ga by applying sol-gel method is reported [36]. The NPs obtained (with size of around 15 nm) were used to study the photocatalytic degradation of organic dye solution (Rhodamine B) as a model pollutant under UV irradiation.…”
Section: Gallium Nps Based Materialsmentioning
confidence: 99%